68.4k views
2 votes
Find the solutions to the following equation:


(x + 1)/(3) - (2x - 1)/(x) = - 1


User Pagep
by
5.3k points

1 Answer

3 votes

Answer:

x=1+/-4i

Explanation:

(x+1)/3-(2x-1)/x=-1

find the common denominator,

in this case, it's going to be 3x.

(x^2+x)/3x-(6x-3)/3x=-1

(x^2+x-6x+3)/3x=-1

x^2-5x+3=-3x

x^2-5x-(-3x)+3=0

x^2-5x+3x+3=0

x^2-2x+3=0

apply the quadratic formula in order to find the roots for x.

Since ax^2+bx+c=0, in this case,

a=1, b=-2, c=3

--------------------------

x=(-b+/-sqrt(b^2-4ac))/2a

x=(2+/-sqrt(4-12))/2

x=(2+/-8i)/2

x=1+/-4i

User Edan Maor
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.